Engineering mesophase stability and structure via incorporation of cyclic terminal groups. Issue 15 (21st March 2022) - Mandle, Richard J.; Abbott, Laurence C.; Fritsch, Luma; Parker, Rachel R.; Hart, Sam; Whitwood, Adrian C.; Cowling, Stephen J.; Moore, John N.; Goodby, John W.
Abstract : The installation of an aliphatic ring at the end of the alkyl chain for a family of 4-alkoxy-4′-cyanobiphenyl liquid crystals is shown to enhance clearing points and promotes the formation of smectic phases, relative to the linear parent materials. Abstract : We report on the characterisation of a number of liquid–crystalline materials featuring cyclic terminal groups, which lead to significant enhancements in the temperature range of the mesomorphic state. Materials with only short terminal chains are able to support lamellar mesophase formation by appending a large terminal cyclic unit at the end of a short spacer composed of methylene units. X-ray scattering experiments reveal that the layer spacings of the lamellar smectic phase are significantly larger when a cyclic end-group is present than for equivalent linear unsubstituted materials, but there is no effect on orientational order. Fully atomistic molecular dynamics simulations faithfully reproduce experimental layer spacings and orientational order parameters, and indicate that the cyclic terminal units spontaneously segregate into diffuse sub-layers and thus cause the increased layer spacing. This shape segregation predicted by molecular dynamics simulations is observed in the crystalline solid state by X-ray diffraction.